Role of Ready-Made Garment Sector in Economic Development of Bangladesh - Uddin, Mohammad Nazim (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2014)
The ready-made garment sector has become an important issue in Bangladesh Economy. The main purpose of the study is to examine the contribution of RMG sector for the development of Bangladesh Economy. The study has used primary and secondary data. In order to collect primary data two sets of questionnaires are developed, which are prepared in the light of the objectives of the study. The secondary data are collected only relevant to the share of GDP, total export value, balance of trade, and employment generation etc. for measuring the economic development of Bangladesh during the period of 2003- 2013. The main reason to consider the certain period is the availability of data. This study revealed that the ready-made garment sector has made substantial contribution for the development of Bangladesh Economy. The result of the study also indicates that the ready-made garment sector in the country has brought the largest part of export earnings that minimize the trade deficit. But it has some realistic problems that retard the growth of ready-made sector. The study seems to carry an enormous academic value since a few studies have been undertaken in this area. It may be helpful to the ready-made garment entrepreneurs, BGMEA, Academic researchers and national policy makers who have been making endeavour to the development of RMG sector as well as Bangladesh Economy as a whole.